2019
DOI: 10.1038/s41467-019-09813-7
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional investigation of the marmoset default mode network

Abstract: The default mode network (DMN) is associated with a wide range of brain functions. In humans, the DMN is marked by strong functional connectivity among three core regions: medial prefrontal cortex (mPFC), posterior parietal cortex (PPC), and the medial parietal and posterior cingulate cortex (PCC). Neuroimaging studies have shown that the DMN also exists in non-human primates, suggesting that it may be a conserved feature of the primate brain. Here, we found that, in common marmosets, the dorsolateral prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(115 citation statements)
references
References 27 publications
3
105
0
Order By: Relevance
“…coupling and directly implicating PV projection neurons in BF-ACC interactions. Further evidence along these lines comes from work in the macaque monkey, where transient BF local field potential activations in the BF in the gamma and other frequency ranges have been shown to precede fluctuations in cortical fMRI deflections (Liu et al, 2019). In addition to reducing exploration behavior, we observed that animals spent increased amounts of time in a state of selfgrooming during BF PV optogenetic stimulation.…”
Section: Bf Electrical Stimulation Modulates Neuropeptide Levels Withsupporting
confidence: 52%
“…coupling and directly implicating PV projection neurons in BF-ACC interactions. Further evidence along these lines comes from work in the macaque monkey, where transient BF local field potential activations in the BF in the gamma and other frequency ranges have been shown to precede fluctuations in cortical fMRI deflections (Liu et al, 2019). In addition to reducing exploration behavior, we observed that animals spent increased amounts of time in a state of selfgrooming during BF PV optogenetic stimulation.…”
Section: Bf Electrical Stimulation Modulates Neuropeptide Levels Withsupporting
confidence: 52%
“…Changes in these subnetworks were consistent with the results of previous cognitive function studies such as those on spatial attention (Rolle et al, 2017), executive function (Liao et al, 2019), and auditory function (Bi et al, 2018) that reference subnetworks in MCI patients. Moreover, the DMN has been regarded as the core part of a functional center (Liu et al, 2019) that is involved in episodic memory and is thought to be the major cognitive domain impaired during early-stage AD (Eyler et al, 2019). That the DMN contains the most distinguishing information for MCI identification was verified using our proposed methods.…”
Section: Discussionmentioning
confidence: 65%
“…2a). Areas of the putative default mode network (DMN), including those in the posterior parietal cortex (PGM, PG, OPt, AIP), posterior cingulate cortex (A23a, A23b) and dorsolateral prefrontal cortex (A8aD, A6DR) lie in the core structure, but not those in the medial prefrontal cortex (A24d, A32, A32V), reflecting recent studies in the marmoset 23,24 .…”
Section: The Connectome Is Dense Heterogeneous and Has High Specifimentioning
confidence: 82%